Information Provision and Postgraduate Studies - Jan Berkes; Frauke Peter; C. Katharina Spiess; Felix Weinhardt (Economica, 2022)
This is the first paper to examine experimentally effects of information provision on beliefs about pecuniary and non-pecuniary returns of postgraduate education, enrolment intentions and realized enrolment. We find that our treatment causally affects beliefs measured six months after treatment. The effects on beliefs differ by gender and academic background, and we find that stated enrolment intentions change accordingly; in particular, males adjust significantly downwards their beliefs and intentions to undertake postgraduate studies. This is driven by males upward adjusting earnings expectations with a first degree only. We follow the students further and provide evidence on actual enrolment one and two years after treatment. Taken together, this study highlights the relevance of information provision on pecuniary and non-pecuniary labour market returns for postgraduate study decisions.
Keywords: 330